Addressing micronutrient deficiency in Cameroon through common bean biofortification - Nchanji, Eileen Bogweh; Siri, Bella; Ngueguim, Martin; Kamdem, Franck; Butare, Louis; Onyango, Patricia; Fungo, Robert (2020)
Biofortification is a process through which the nutritional value – vitamins or minerals of a food crop is enhanced through conventional breeding. Through biofortification, vitamins and minerals such as iron, zinc, provitamin A etc. are enhanced. Eleven high iron and zinc beans have been released in Cameroon after a recent nutritional screening of more than 30 common bean varieties (local landraces and improved bean varieties). The adoption and dissemination of these newly identified high iron and zinc varieties will contribute to addressing iron and zinc deficiency among women and children under five. Growing and selling beans will also ensure income and food security for the household. Common beans are the most grown and consumed legume and affordable source of protein in Cameroon. The release of high iron and zinc beans and subsequent incorporation into the household diets is a cost-effective intervention in addressing health disorders related to inadequate intake of iron and zinc.